Numerical analysis of metro station pit dewatering and its influence - Ma, Zongyuan; Tang, Shitong; Yang, Zhiguo (Frontiers in Earth Science, 2023)
The underground water level in Xi'an city is generally shallow, and the excavation of the deep foundation pit mainly needs underground water dewatering. The ground deformation due to the dewatering and its influences should be fully analyzed. The empirical formula estimates the water inflow of the foundation pit, and the process of dewatering and metro station construction is simulated via the finite element method and the theory of soil consolidation according to the field investigation and survey data of the natural geological and hydrological environment. The time of water level falling and recovery, ground settlement, and strata deformation caused by pit dewatering and excavation are predicted. The analysis results of the ground settlement are within reasonable limits and close to the previous metro projects. Finally, the influence of groundwater dewatering on Xi'an Metro Line 14 is discussed. The settlement indued by dewatering for constructing a metro station in the sandy stratum is relatively small, and the loess stratum has the most significant dewatering settlement. The proportion of settlement due to dewatering of the station construction in the loess stratum is nearly 1/3 versus the total land subsidence.